Effectiveness of the Swachh Bharat Mission and barriers to ending open defecation in India: a systematic review - VerKuilen, Anna; Sprouse, Lauren; Beardsley, Rachel; Lebu, Sarah; Salzberg, Aaron; Manga, Musa (Frontiers in Environmental Science, 2023)
In 2016, nearly 60% of the population of India open defecated, which was 4 times the global rate, and reducing open defecation (OD) in India will be essential in meeting the 2030 Sustainable Development Goals 6.2 and improving global public health. The government of India launched the Swachh Bharat Mission (SBM) in 2014 to make all Indian states OD-free (ODF) by 2019. Despite reports from the Government of India on the success of SBM, the true ODF status of Indian states is still unknown. A systematic review of the peer-reviewed literature was conducted to assess the impact of SBM on OD in India, evaluate the successes and shortcomings of SBM in reducing OD, and provide recommendations for future interventions to reduce or eliminate OD in India. A total of 237 publications were screened, and 22 were selected for inclusion. While the Prime Minister declared India ODF in 2019, studies suggest that the government monitoring system overestimates numbers of ODF villages and toilet coverage. Reasons for households’ continued OD practice include financial constraints, lack of water supply, governmental mistrust, cultural beliefs, and personal preference. Community incentives and penalties have been used to encourage proper sanitation practices with varying success. Overarching strategies and approaches that have worked well across study districts to reduce OD include high involvement of district leadership and innovative behavior-change and local community mobilization campaigns.